Acidity tuning of montmorillonite K10 by impregnation with dodecatungstophosphoric acid and hydroxyalkylation of phenol - Garade, Ajit C.; Kshirsagar, V. S.; Mane, R. B.; Ghalwadkar, Ajay A.; Joshi, U. D.; Rode, C. V. (Applied Clay Science, 2010)
Acidity tuning of montmorillonite K10 (mont K10) was achieved by impregnating with dodecatungstophosphoric acid (DTP). The effect on the hydroxyalkylation of phenol was studied at 353 K with phenol to formaldehyde molar ratio of 5. The nature and strength of acid sites were determined by NH(3)-TPD measurement while the distribution of Brensted and Lewis acid sites expressed as B/L ratio, was determined by pyridine IR technique. Among various loadings of DTP (5-60%) studied for the hydroxyalkylation of phenol, 20% DTP/mont K10 showed the highest catalyst activity (90% selectivity to bisphenol F with 28% conversion of phenol). Both total concentration of acid sites and the distribution of acid sites in a high temperature region were required for the high bisphenol F selectivity. Our catalyst (20% DTP/Mont K10) could be recycled three times. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acidity tuning; Dodecatungstophosphoric acid/Montmorillonite K10; Hydroxyalkylation; Impregnation; Temperature programmed desorption

Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Selective hydrogenolysis of glycerol to 1,2-propanediol: comparison of batch and continuous process operations - Rode, Chandrashekhar V; Ghalwadkar, Ajay A.; Mane, R. B.; Hengne, Amol M.; Jadkar, Sachin T.; Biradar, Narayan S. (Organic Process Research & Development, 2010)
The screening of copper chromite catalysts with various promoters such as Al, Zn, and Ba for glycerol hydrogenolysis to 1,2-propanediol (1,2-PDO) in a batch reaction showed that Cu-Cr (Ba) catalyst gave the highest conversion of 34% and selectivity of 84% to 1,2-PDO. In a continuous operation (23 g catalyst bed) the same catalyst showed higher conversion of glycerol and selectivity for 1,2-PDO of 65% and > 90%, respectively, with an on-stream activity of similar to 800 h. Better performance in a continuous operation could be due to the in situ activation of the catalyst, suppression of glycerol cracking to ethylene glycol, as well as excessive hydrogenation of 1,2-PDO to 2-propanol due to lower contact time of 1.3 h as compared to that in a batch operation (5 h). Effects of various process parameters on conversion and selectivity also have been compared for batch and continuous operations.

Role of promoters in copper chromite catalysts for hydrogenolysis of glycerol - Mane, R. B.; Ghalwadkar, Ajay A.; Hengne, Amol M.; Suryawanshi, Y. R.; Rode, C. V. (Catalysis Today, 2011)
Various copper chromite catalysts with and without promoters were prepared by simultaneous co-precipitation and digestion technique and the role of promoters (Al, Ba and Zn) was investigated for hydrogenolysis of glycerol to 1,2-propylene glycol (1,2-PG) in both batch and continuous operations. Among various promoters studied, copper chromite catalyst with Ba as a promoter showed the highest activity and selectivity of 85% to 1,2-PG. This catalyst was found to be active for more than 800 h in a continuous operation also. Ammonia TPD results showed that barium promoted copper chromite catalyst had the highest acidity which facilitates the dehydration of glycerol to acetol which is the first step in hydrogenolysis of glycerol to 1,2-PG. The effect of barium content and variation in the promoters combination was also studied. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propylene glycol; Acetol; Ammonia TPD; Glycerol hydrogenolysis; Surface acidity